Band pass filter comparison of Hairpin line and square open-loop resonator method for digital TV community - Budi Prasetya; Yuyun Siti Rohmah; Dwi Andi Nurmantris; Sarah Mulyawati; Reza Dipayana (Institute of Advanced Engineering and Science, 2021)
The selection of the right filter design method is a very important first step for a radio frequency engineer. This paper presents the comparison of two methods of band pass filter design using hairpin-line and square open-loop resonator. Both methods were applied to obtain filter designs that can work for broadcasting system in digital television community. Band pass filter was simulated using design software and fabricated using epoxy FR-4 substrate. The results of simulation and measurement shown return loss value at 27.3 dB for hairpin line band pass filter and 25.901 for square open-loop resonator band pass filter. Voltage standing wave ratio parameter values were 1.09 and 1.1067 for hairpin line and square open-loop band pass filter respectively. The insertion loss values for the Hairpin line band pass filter and square open-loop band pass filter were 0.9692 and near 0 dB, respectively. Fractional bandwidth, for hairpin line band pass filter, was 6.7% while for square open-loop band pass filter was 4.8%. Regarding the size, the dimension of square open-loop resonator was approximately five times larger than hairpin-line band pass filter. Based on the advantages of the hairpin line method, we recommend that researchers choose the filter for digital TV broadcasting.